Some Approximation Properties of Certain $q$-Baskakov-Beta Operators (Analysis in Theory and Applications, 2016)
In this paper, we propose the $q$ analogue of modified Baskakov-Beta operators. The Voronovskaja type theorem and some direct results for the above operators are discussed. The rate of convergence and weighted approximation by the operators are studied.